The Pedagogic Value of Children’s Literature (Rupandehi Campus Journal, 2024)
The texts of children’s literature have unique features and the language teachers still have limited ideas on how these texts support language learning. At this juncture, this article aims at exploring the value of children’s literature in language learning. Simple, interesting and linguistically rich texts of children’s literature make classroom environment conducive to learn. These texts engage students in different communicative and cooperative tasks: pair and group discussions, jigsaw, simulation and role play. These texts contribute to students’ language enrichment, development of communicative competence, inferential, and interpretive skills and ultimately lead them to creative writing. Children’s literature is pedagogically crucial for students and teachers.